An effectiveness study of hand, foot and mouth disease prevention and control measures in child care centers - เลิศสุโภชวณิชย์ สมนึก; คงอยู่ สมคิด; ฮิ้นจ้อย เสาวพักตร์; สุขเกษม ปรารถนา; กิจผาติ รุ่งเรือง (Disease Control Journal, 2014)
Hand, foot and mouth disease was a major public health problem among children. A two-thirds majority of cases from a reporting of national disease surveillance system were occurred in child care centers and kindergartens. The study aimed to assess an effectiveness of hand, foot and mouth disease prevention and control measures in child care centers. A comparative study was conducted to find an association of decreasing morbidity rate in districts, where the sampled child cares were located and the child care centers, which was certified for standardized prevention and control measures in communicable diseases by Department of Disease Control, Ministry of Public Health. A cluster sampling by provinces and districts and simple random sampling were completed for all registered child care centers in Thailand. Univariate analysis and multiple logistic regressions were conducted to determine the effectiveness of hand, foot and mouth disease prevention and control measures. A total of 260 child care centers from 10 provinces in 16 districts and 108 sub- districts were participated in the study. The certified child care centers for standardized prevention and control measures in communicable diseases effected to decreasing trend in the morbidity rate of hand, foot and mouth disease in the areas. The child care centers with having a policy for a management of disease prevention and control, child’ร isolating illness effectively, a personal glass for drinking sufficient latrine, separation of toilet and shower room and sufficient personal protective equipment were significantly associated with decreasing trend in morbidity rate of hand, foot and mouth disease. The outcome of this study showed a successful program of prevention and control measures in communicable diseases and the program should be expanded in other sectors.